Hydrobiology of Pokkali Fields of Rice Reaserch Station ,Ernakulam - Drona Sarkar (Department of Fishery Hydrography, 2013)
Abstract- A comprehensive study was undertaken to assess water and soil quality of pokkali rice fields in Ernakulam district of Kerala during traditional paddy cultivation period from June to October 2012 and the tidal exchange period from November to May 2013. The seasonal changes of hydrographical parameters and sediment characteristics were studied. The zooplankton and fishes found in the study area were identified. The water temperature was maximum during premonsoon period and minimum during southwest monsoon. Negative correlation was found with pH. The water was slightly acidic during the rice cultivation and alkaline during the tidal exchange in all the three sites. Salinity was very low during the rice cultivation due to the southwest monsoon. and showed higher values during the other seasons. Dissolved oxygen was low in the rice field near to the highly polluted feeder canal. It decreased with increase in salinity. Alkalinity showed lower values during the summer months. Nutrients were very low in the fields. Ammonia-N was low during the rice cultivation and highest during the dry period. The lowest values were seen for Nitrite-N and phosphate-P. Maximum total organic carbon observed during the pre-monsoon seasons. Sediment contains maximum sand followed by silt and clay. Statistical analysis of the seasonal variation with one way ANOVA showed significant difference among the mean values of salinity, alkalinity, ammonia, nitrite and phosphate for the four seasons (P< 0.01).On the other hand temperature and dissolved oxygen showed significant difference among the three sites. Dominant groups of zooplankton found in the pokkali fields were copepods, rotifers, crustacean larvaes and cladocerans. Among the crustaceans Feneropenaeus indicus were the most important species. Mainly juveniles contributed to the shrimp catch. The dominant groups of fishes were Oreochromis mossambicus and Channa sp. durng the prawn filtration period.